PENGELOLAAN MOBIL DINAS PEMERINTAH KOTA PEKANBARU OLEH BADAN ASET MENURUT PERATURAN PEMERINTAH NOMOR 27 TAHUN 2014 TENTANG PENGELOLAAN BARANG MILIK NEGARA/DAERAH - Elisa, Kiki; Indra, Mexsasai; ', Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Seeing the use of official cars by the day , the authors observe is often used to transport goods , the driver changing, and perhaps drove different way to when driving a private car . Private car seems to be well maintained , used with affection , driven with care / not rude , turn persenelingnya conducted in accordance with the speed of the car , so it is not quickly broken. Kind of this research is empirical jurisdiction, namely by approaching problems examined with real law in accordance with the reality on the ground. In this study the authors directly conduct research on the location or point studied to provide complete the problem. This research conducted in Pekanbaru City and Financial Management Board and the Regional Asset. Population and sample are those relating to the issue, examined in this study, the source of the data used is a primary data, secondary data and data tertiary. Data collection techniques in this study is observation, interview and literature study. From the research, there are three main problems can be inferred. First, Is the management of official cars by the government of Pekanbaru are in accordance with Government Regulation Number 27 of 2014? What are the limiting factor in the implementation of the management of official cars for government officials in the city of Pekanbaru? And Efforts natural assets management agency carbuncle car Pekanbaru City Government? Advice writer first, Expected created a special rule regarding the collection of official cars so that there is no official car of excess or less in each SKPD. Secondly, It is expected that the government can impose sanctions that have a deterrent effect . So that users do maintenance official car of the official car of possession.Keywords: Management – Official Car